The ANALISIS BIBLIOMETRIK GLOBAL TREN PERKEMBANGAN INFORMASI SISTEM DAN INFORMASI TEKNOLOGI - Adyaksa, Adyaksa; Huda, Ahmad Nawirul; Firmansyah, Haris Furkon Hasbi; Fadlullah, Muhammad Zidan; Yahya, Ahmad Bimo Wiranata (STKIP Pesisir Selatan, 2025)
This research aims to provide a clearer overview of the development of information systems and technology topics. Furthermore, bibliometric analysis using Scopus metadata revealed that the most productive author was Anon, J.C.R., with 100 documents, followed by Nagy, Paul G. with 4 documents, and Saranto, Kaija K., Bates, David D.B., Dimick, Chris, and Janicki, Thomas N., each contributing 3 documents. The author with the highest impact, based on h-index, was Añón, J.C.R. with an h-index of 15.Among journals, the International Journal of Medical Informatics was highly influential, featuring 14 relevant articles, an h-index of 10, and a g-index of 14, indicating a high number of cited articles. With 489 citations since 1997, this journal has had a major impact on medical informatics. Following closely was the Journal of Information Systems Education, which had 12 relevant articles, an h-index of 9, a g-index of 12, and 210 citations since 2013.Publications related to information systems, information technology, and education fluctuated between 1997 and 2023. The peak of productivity occurred in 2008, with over 40 publications, followed by a sharp decline until 2009. A slight recovery was observed in 2010 before another significant drop in 2023, with only 18 articles. However, in 2024, a slight rebound emerged, with the number of articles rising to 20, suggesting fluctuating trends.